Glucocorticoids alter neuronal differentiation of human neuroepithelial-like cells by inducing long-lasting changes in the reactive oxygen species balance. (August 2016) - Raciti, Marilena; Ong, Jennie; Weis, Laura; Edoff, Karin; Battagli, Cristina; Falk, Anna; Ceccatelli, Sandra
Abstract: Prenatal exposure to excess glucocorticoid has been shown to have adverse effects on the developing nervous system that may lead to alterations of fetal and adult neurogenesis, resulting in behavioral changes. In addition, an imbalance of the redox state, with an increased susceptibility to oxidative stress, has been observed in rodent neural stem cells exposed to the synthetic glucocorticoid analog dexamethasone (Dex). In the present study, we used the induced pluripotent stem cells (IPSC)-derived lt-NES AF22 cell line, representative of the neuroepithelial stage in central nervous system development, to investigate the heritable effects of Dex on reactive oxygen species (ROS) balance and its impact on neuronal differentiation. By analysing gene expression in daughter cells that were never directly exposed to Dex, we could observe a downregulation of four key antioxidant enzymes, namely Catalase, superoxide dismutase 1, superoxide dismutase 2 and glutathione peroxidase7, along with an increased intracellular ROS concentration. The imbalance in the intracellular REDOX state was associated to a significant downregulation of major neuronal markers and a concomitant increase of glial cells. Interestingly, upon treatment with the antioxidant N-acetyl-cysteine (NAC), the misexpression of both neuronal and glial markers analyzed was recovered. These novel findings point to the increased ROS concentration playing a direct role in the heritable alterations of the differentiation potential induced by Dex exposure. Moreover, the data support the hypothesis that early insults may have detrimental long-lasting consequences on neurogenesis. Based on the positive effects exerted by NAC, it is conceivable that therapeutic strategies including antioxidants may be effective in the treatment of neuropsychiatric disorders that have been associated to increased ROS and impaired neurogenesis. Highlights: Dexamethasone induces heritable alterations in the differentiation potential of lt-NES. Neuronal differentiation is inhibited whereas the number of glial cells increases. The differentiation impairment of lt-NES is mediated by an unbalanced REDOX status.